Applying Metacognition Through Patient Encounters and Illness Scripts to Create a Conceptual Framework for Basic Science Integration, Storage, and Retrieval - Hennrikus, Eileen F (J Med Educ Curric Dev, 2018)
PROBLEM: Medical school curriculum continues to search for methods to develop a conceptual educational framework that promotes the storage, retrieval, transfer, and application of basic science to the human experience. To achieve this goal, we propose a metacognitive approach that integrates basic science with the humanistic and health system aspects of medical education. INTERVENTION: During the week, via problem-based learning and lectures, first-year medical students were taught the basic science underlying a disease. Each Friday, a patient with the disease spoke to the class. Students then wrote illness scripts, which required them to metacognitively reflect not only on disease pathophysiology, complications, and treatments but also on the humanistic and health system issues revealed during the patient encounter. Evaluation of the intervention was conducted by measuring results on course exams and national board exams and analyzing free responses on the illness scripts and student course feedback. The course exams and National Board of Medical Examiners questions were divided into 3 categories: content covered in lecture, problem-based learning, or patient + illness script. Comparisons were made using Student t-test. Free responses were inductively analyzed using grounded theory methodology. CONTEXT: This curricular intervention was implemented during the first 13-week basic science course of medical school. The main objective of the course, Scientific Principles of Medicine, is to lay the scientific foundation for subsequent organ system courses. A total of 150 students were enrolled each year. We evaluated this intervention over 2 years, totaling 300 students. OUTCOME: Students scored significantly higher on illness script content compared to lecture content on the course exams (mean difference = 11.1, P = .006) and national board exams given in December (mean difference = 21.8, P = .0002) and June (mean difference = 12.7, P = .016). Themes extracted from students’ free responses included the following: relevance of basic science, humanistic themes of empathy, resilience, and the doctor-patient relationship, and systems themes of cost, barriers to care, and support systems. LESSONS LEARNED: A metacognitive approach to learning through the use of patient encounters and illness script reflections creates stronger conceptual frameworks for students to integrate, store, retain, and retrieve knowledge.